Immunological basis of early clearance of Mycobacterium tuberculosis infection: the role of natural killer cells. (5th January 2021) - Abebe, F.
Summary: Tuberculosis (TB) kills more people than any other single infectious disease globally. Despite decades of research, there is no vaccine to prevent TB transmission. Bacille Calmette–Guérin (BCG) vaccine, developed a century ago, is effective against childhood (disseminated and miliary) TB. However, its protective efficacy against pulmonary TB varies from 0 to 80% in different populations. One of the main reasons for the lack of an effective vaccine against TB is the lack of complete understanding about correlates of protective immunity on which to base vaccine design and development. However, some household contacts who are extensively exposed to Mtb infection remain persistently negative to tuberculin skin test and interferon‐gamma assay. These individuals, called 'resisters', clear Mtb infection early before the development of acquired immunity. The immunological basis of early Mtb clearance is yet to be established; however, innate lymphocytes such as monocytes/macrophages, dendritic cells, neutrophils and natural killer cells, and innate‐like T cells such as mucosal‐associated invariant T cells, invariant natural killer (NK) T cells and gamma‐delta (γδ) T cells, have been implicated in this early protection. In recent years, NK cells have attracted increasing attention because of their role in controlling Mtb infection. Emerging data from animal and epidemiological studies indicate that NK cells play a significant role in the fight against Mtb . NK cells express various surface markers to recognize and kill both Mtb and Mtb ‐infected cells. This review presents recent advances in our understanding of NK cells in the fight against Mtb early during infection, with emphasis on cohort studies. Abstract : The paper summarizes our current understanding of early clearance of Mycobacterium tuberculosis infection in some resistant individuals, with special emphasis on the role natural killer cells.